Microclimate modification through shading and watering frequency treatments as efforts for ex situ conservation of pule pandak (Rauvolfia serpentina) (Asian Journal of Agriculture, 2017)
Abstract. Samanhudi, Purwanto E, Sulandjari, Setiyaningsih A. 2017. Microclimate modification through shading and watering frequency treatments as efforts for ex-situ conservation of pule pandak (Rauvolfia serpentina). Asian J Agric 1: 35-39. Pule pandak (Rauvolfia serpentina Benth) is a rare medicinal plant. To meet the needs of the drug, people continue to explore nature. Thus, proper cultivation technique for R. serpentina is required, by giving appropriate shading level and watering frequency to the growth and yield of R. serpentina. This research aimed to examine the effects of shading and watering frequency on the growth and yield of R. serpentina. The study was conducted from February to July 2009 in BBP Mondromino, Pokoh Village, Wonogiri at 141 meters above sea level. The experimental design used in this research was a Split Plot Design, which consisted of two factors and three repetitions. The first factor (main plot) was a shading level that consisted of three levels: 55%, 65%, and 75%. The second factor (subplot) was watering frequency that consisted of three levels: once every three days, once every five days and once every seven days. Data were subjected to analysis of variance, followed by post hoc test of Duncan Multiple Range Test at 5% level. The reserpine content was analyzed descriptively. The results showed that no interaction between shading level and watering frequency was seen on all variables. The shading level caused no significant effect on growth and yield of R. serpentina, except the leaf area. Watering frequency caused no significant effect on growth and yield of R. serpentina, apart from the chlorophyll content. The results showed that plants treated with watering frequency of five-day intervals produced the highest chlorophyll content. Plants treated with shading level of 65% and watering frequency of once every five days produced the highest reserpine content.
Keywords: Pule pandak; Rauvolfia serpentine; reserpine shading; watering frequency